Chang qing formula ameliorates colitis-associated colorectal cancer via suppressing IL-17/NF-κB/STAT3 pathway in mice as revealed by network pharmacology study - Luo, Qihan; Huang, Shuo; Zhao, Lisha; Liu, Jingqun; Ma, Qing; Wang, Yiheng; Dong, Yu; Li, Changyu; Qiu, Ping (Frontiers in Pharmacology, 2022)
Colitis-associated colorectal cancer (CAC) is a specific type of colorectal cancer (CRC) with high mortality and morbidity, the chronic inflammation in the intestinal mucosal is the characteristic of CAC. Chang Qing formula (CQF) is a Chinese herbal formula used clinically for the treatment of CAC with remarkable clinical efficacy, but its mechanism remains unclear. In the present work, Combined network pharmacology and transcriptomics were used to analyze the potential active ingredients and elucidate molecular mechanism of CQF in treating CAC. Firstly, the constituents migrating to blood of CQF were analyzed and identified by UPLC-Q-TOF-MS/MS, and core genes and pathways were screened by network pharmacology analysis. Encyclopedia of Genes and Genomes (KEGG) analysis showed that the IL-17 signaling pathway involved in CAC may be closely associated with the potential mechanism of action of CQF. Subsequently, the results from animal studies indicated that CQF profoundly reduced tumor numbers and tumor size in AOM/DSS mice. The RNA-seq data was analyzed utilizing Ingenuity Pathway Analysis (IPA), and the results supported the idea that CQF exerts a tumour-suppressive effect via the IL-17 signaling pathway. Further studies demonstrated that CQF significantly reduced IL-17A levels, which in turn inhibited NF-κB/IL-6/STAT3 signaling cascade, suppressed MMP9 expression and promoted tumor cell apoptosis. In conclusion, the current study demonstrated that CQF remarkably improved inflammatory tumor microenvironment, and hindered the transformation of inflammation into cancer. These findings may help to design future strategies for the treatment of CAC.